2005
DOI: 10.1007/s10935-005-0003-y
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Culturally Relevant Violence Prevention Models on School-Age Youth

Abstract: The Family and Community Violence Prevention (FCVP) Program was established in 1994 to address the escalation of youth violence among ethnic minorities. This federally funded program adapted the public health model and organized Family Life Centers throughout the country to serve youth who were considered to be at risk for violence and other abusive behaviors. The purpose of this three-year study, 1999-2002, was to determine the effectiveness of the FCVP Program's six-component curriculum in reducing violence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 7 publications
0
30
0
Order By: Relevance
“…First, researchers have examined the Family and Community Violence Program (FCVP), which was originally designed around the public health model using the Social Learning Theory. This program was most effective at younger ages, lending support for early interventions (Rodney et al, 2005). Other prevention models are based around education and positive youth development.…”
Section: Programsmentioning
confidence: 94%
See 2 more Smart Citations
“…First, researchers have examined the Family and Community Violence Program (FCVP), which was originally designed around the public health model using the Social Learning Theory. This program was most effective at younger ages, lending support for early interventions (Rodney et al, 2005). Other prevention models are based around education and positive youth development.…”
Section: Programsmentioning
confidence: 94%
“…Previous research has indicated that moderate student involvement is often times considered a safety strategy (Rodney et al, 2005). By focusing on after-school activities, it is less likely that these adolescents will exhibit academic problems or contribute to delinquency.…”
Section: Factor Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…= .077 to .230, p < .001) (Brody et al, 2006) to .279 (95% C.I. = .155 to .403, p < .001) (Rodney, Johnson, & Srivastava, 2005). These findings suggest the results are relatively robust, at least at this level of analysis.…”
Section: Meta-analysis Of Overall Csi Effectivenessmentioning
confidence: 67%
“…Programs that targeted ethnic minority youth often employed intervention and risk prevention based strategies, implemented through culturally relevant curriculum and pedagogy. Examples of these programs include Family and Community Violence Prevention (Rodney, Johnson, & Srivastava, 2005), Families and Schools Together (FAST); (Guerra, & Knox, 2008), and Joven Noble (Tello, Servantes, Cordova, & Santos, 2010). Other programs include those that promote college outreach and support (Denner, Cooper, Dunbar, & Lopez, 2005;Diversi & Mecham, 2005;Hishinuma, Chang, Sy, Greaney, Morris, Scrance, et al, 2009;Larson & Walker, 2006;Riggs, Bohnert, Guzman, & Davidson, 2010).…”
Section: Youth Empowerment and Leadershipmentioning
confidence: 99%